Spontaneous spin squeezing in a rubidium BEC - Théo Laudat; Vincent Dugrain; Tommaso Mazzoni; Meng-Zi Huang; Carlos L Garrido Alzar; Alice Sinatra; Peter Rosenbusch; Jakob Reichel (New Journal of Physics, 2018)
We describe an experiment where spin squeezing occurs spontaneously within a standard Ramsey sequence driving a two-component Bose–Einstein condensate (BEC) of ^87 Rb atoms trapped in an elongated magnetic trap. The squeezing is generated by state-dependent collisional interactions, despite the near-identical scattering lengths of the spin states in ^87 Rb. In our proof-of-principle experiment, we observe a metrological spin squeezing that reaches 1.3 ± 0.4 dB for 5000 atoms, with a contrast of 90 ± 1%. The method may be applied to realize spin-squeezed BEC sources for atom interferometry without the need for cavities, state-dependent potentials or Feshbach resonances.